Paleogene Fossil Birds - Mayr, Gerald. (Springer Berlin Heidelberg, 2009)
The present book is the first detailed review of the Paleogene avian fossil record on a worldwide scale. Numerous well-preserved fossil bird remains from this geological period, which covers the time span from the end of the Mesozoic era to the beginning of the Miocene, have been described in the past two decades. Some of these not only provide information on morphological transformations in the evolutionary history of the extant avian taxa, but are also of great significance for an understanding of their historical biogeography. Others represent extinct taxa which sometimes show a bizarre morphology not found in modern birds, such as the giant pseudo-toothed birds which reached wingspans up to six meters. The reader is introduced to basic morphological features of the various groups which, as far as possible, are placed into a phylogenetic context in the light of current hypotheses on the interrelationships of extant birds. In a concluding chapter the biogeographical significance of Paleogene fossil birds and possible reasons for faunal changes during the Paleogene are detailed. As such, the book not only aims at providing an overview for specialists, but may also help students of other fields of vertebrate paleontology to better understand Paleogene ecosystems.